Comparative design, hydrodynamic analysis, and physical performance of fish-like robots - Glaze, J.; Salazar, R.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (Elsevier, 2021)
Biological aquatic animals are turned to for design inspiration of marine drones because of their efficient long-range performance and high agility in the water. Investigations of body caudal fin biological shapes from the Carangiform, Subcarangiform, and Thunniform categories are compared to widely used symmetric airfoils to determine shape performance. Three-dimensional hydrodynamic results using four solution methods are examined to analyze these hydrofoils at decreasing aspect ratios with a constant wing chord length. This numerical investigation results in the selection of the Subcarangiform hydrofoil to be used in the physical design of a fish-like bio-inspired drone. These hydrodynamic results are utilized to adapt a fish-like aquatic unmanned vehicle from conceptual design to working prototype that is tested in a mission environment. Parameters for buoyancy and stability are then defined to give guidance during the physical design phase. Quantities for weight and volume could be extrapolated and used to determine the need for ballast in the system. The final prototype system is tested in its mission environment. It accomplishes turns at a body length to turn radius ratio of 1:1, at a swim velocity of 1.5 body lengths per second. This system's real-world performance is compared to that of other systems.